2013
DOI: 10.1016/j.pain.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Association of serotonin-1A and -2A receptor promoter polymorphisms with depressive symptoms, functional recovery, and pain in patients 6 months after lumbar disc surgery

Abstract: Single nucleotide polymorphisms (SNPs) in the serotonergic (5HT) system seem to have modulatory effects on depression and physical function. Preliminary evidence suggests that gene×environment interactions play a role in the development of depression, with somatic complaints serving as environmental stressors. We hypothesized that pain intensity may serve as a stress factor that modulates the association between SNPs in the 5HT system and depression. We investigated symptoms of pain, depression, physical funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
2
28
1
Order By: Relevance
“…148 In agreement, several studies have shown that life stressors, including chronic pain or infection, interact with the rs6295 genotype for anxiety, depression and susceptibility to hospitalization for depression. 51,81,146,[149][150][151] However, in 1 study, although the G allele, childhood or later life stress were each associated with substance abuse, psychiatric hospitalization and suicide, there was no interaction between genotype and trauma in a highly stressed cohort. 61 Similarly, other studies did not find an association between rs6295/ stress and depression.…”
Section: Environmental Risk: Stress × Genotype Interactionmentioning
confidence: 65%
See 1 more Smart Citation
“…148 In agreement, several studies have shown that life stressors, including chronic pain or infection, interact with the rs6295 genotype for anxiety, depression and susceptibility to hospitalization for depression. 51,81,146,[149][150][151] However, in 1 study, although the G allele, childhood or later life stress were each associated with substance abuse, psychiatric hospitalization and suicide, there was no interaction between genotype and trauma in a highly stressed cohort. 61 Similarly, other studies did not find an association between rs6295/ stress and depression.…”
Section: Environmental Risk: Stress × Genotype Interactionmentioning
confidence: 65%
“…In terms of physiologic differences, rs6295 G carriers showed thermal hypoalgesia 80 and increased depression after lumbar surgery. 81 In panic patients with disorder/agoraphobia with the GG genotype, there was increased amygdala reactivity to threat or safety cues, behavioural avoidance and reduced response to cognitive behavioural therapy, 82 and increased contextual fear in healthy participants. 83 Similarly, in panic disorder the G allele was associated with increased amygdala reactivity to fearful faces, 56 while in healthy controls an opposite association was seen, 52 suggesting that the influence of the polymorphism may depend on the disease state.…”
Section: Htr1a Rs6295 and Phenotypic/brain Network Alterationsmentioning
confidence: 99%
“…In one study, the strongest association was seen in patients with depression and comorbid anxiety (Molina et al, 2011). Adult stress, but not early life stress, in combination with the risk G-allele increases the association with increased stress reactivity, depression and suicide (Wasserman et al, 2006; Benedetti et al, 2011; Mekli et al, 2011; Lebe et al, 2013). However in a larger study of normal subjects no such associations were found (Chipman et al, 2010).…”
Section: Transcriptional Modifiers Of 5-ht1a Receptor Expression In Amentioning
confidence: 99%
“…Our study does not support this hypothesis in older adults. Previous reports of significant associations between the investigated genetic variants in HTR1A , COMT , and FKBP5 , adverse environmental exposure and risk for depression relied on few patients with depression who had the investigated genotype and who were also exposed to stress adverse environmental exposure and risk for depression relied on few patients with depression who had the investigated genotype and who were also exposed to stress (Galvão-de Almeida et al, 2014; Kraus et al, 2007; Lebe et al, 2013; Comasco et al, 2011; Doornbos et al, 2009; Mandelli et al, 2007; Appel et al, 2011; Kang et al, 2012; Lahti et al, 2015; Nyman et al, 2011; Scheuer et al, 2016; Shinozaki et al, 2011; Zimmermann et al, 2011). Our study, with a large number of cases, does not support an omnipresent existence of interactions between these genetic variants and adverse environmental exposures on risk for depression.…”
Section: Discussionmentioning
confidence: 99%